Type 1 diabetes structured education: what are the core self‐management behaviours?. Issue 6 (21st March 2013) - Grant, L.; Lawton, J.; Hopkins, D.; Elliott, J.; Lucas, S.; Clark, M.; MacLellan, I.; Davies, M.; Heller, S.; Cooke, D.
Abstract Aims Study aims were to (1) describe and compare the way diabetes structured education courses have evolved in the UK, (2) identify and agree components of course curricula perceived as core across courses and (3) identify and classify self‐care behaviours in order to develop a questionnaire assessment tool. Methods Structured education courses were selected through the Type 1 diabetes education network. Curricula from five courses were examined and nine educators from those courses were interviewed. Transcripts were analysed using framework analysis. Fourteen key stakeholders attended a consensus meeting, to identify and classify Type 1 diabetes self‐care behaviours. Results Eighty‐three courses were identified. Components of course curricula perceived as core by all diabetes educators were: carbohydrate counting and insulin dose adjustment, hypoglycaemia management, group work, goal setting and empowerment, confidence and control. The broad areas of self‐management behaviour identified at the consensus meeting were carbohydrate counting and awareness, insulin dose adjustment, self‐monitoring of blood glucose, managing hypoglycaemia, managing equipment and injection sites; and accessing health care. Specific self‐care behaviours within each area were identified. Conclusions Planned future work will develop an updated questionnaire tool to access self‐care behaviours. This will enable assessment of the effectiveness of existing structured education programmes at producing desired changes in behaviour. It will also help people with diabetes and their healthcare team identify areas where additional support is needed to initiate or maintain changes in behaviour. Provision of such support may improve glycaemia and reduce diabetes‐related complications and severe hypoglycaemia.